2013
DOI: 10.1051/m2an/2012053
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model of Blood Flow in an Anatomically Detailed Arterial Network of the Arm

Abstract: Abstract.A distributed-parameter (one-dimensional) anatomically detailed model for the arterial network of the arm is developed in order to carry out hemodynamics simulations. This work focuses on the specific aspects related to the model set-up. In this regard, stringent anatomical and physiological considerations have been pursued in order to construct the arterial topology and to provide a systematic estimation of the involved parameters. The model comprises 108 arterial segments, with 64 main arteries and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 44 publications
1
40
0
2
Order By: Relevance
“…The method of radial artery point has been used by Chinese medicine for thousands of years, to obtain more information about human body and some diseases. In 2013, Watanabe et al 15 focussed on the arterial network of the arm; the model comprised 108 arterial segments with 63 main arteries and 44 perforator arteries, with lumen radii ranging from 0.24 cm axillary artery to 0.018 cm perforator arteries, which was a complicated project. Furthermore, their results of pressure wave and flow rate were in agreement with patients’ records already published in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The method of radial artery point has been used by Chinese medicine for thousands of years, to obtain more information about human body and some diseases. In 2013, Watanabe et al 15 focussed on the arterial network of the arm; the model comprised 108 arterial segments with 63 main arteries and 44 perforator arteries, with lumen radii ranging from 0.24 cm axillary artery to 0.018 cm perforator arteries, which was a complicated project. Furthermore, their results of pressure wave and flow rate were in agreement with patients’ records already published in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…4 C represents the fourth-order Hookean elasticity tensor and ε s is the elastic strain tensor. The material properties of the structure are fully determined by the Young's modulus, E, and the Poisson's ratio, ν.…”
Section: Elasticity Of the Vascular System Modelmentioning
confidence: 99%
“…Although many attempts have been made to model blood flow in the cardiovascular system during the past decades, three dimensional simulation of the whole vascular system is still an unfeasible task because of the complexity of the cardiovascular system that consists of millions of vessels spanning several orders of magnitude in size. Therefore, previous studies reported in the literature include simplified lumped parameter and one dimensional flow models [3][4][5][6]. The lumped parameter models are based on an analogy between the current flow in an …”
Section: Introductionmentioning
confidence: 99%
“…Os modelos utilizados para a geração deárvores arteriais podem ser classificados como: anatômicos [13], a parâmetros condensados [4], fractais [12,14] e otimizados [1,3,7,10]. Na linha de pesquisa deste trabalho, destacam-se os modelos otimizados deárvores circulatórias gerados pelo método CCO (Constrained Constructive Optimization) [8].…”
Section: Introductionunclassified